Climate change, impacts and mitigation: Nigerian experience (2010)
Climate has continued to change for millennia. The various anthropogenic factors have accelerated the change to the extent that what used to be subtle natural changes have become measurable and observable changes. These anthropogenic factors have resulted in the generation of greenhouse gases (GHGs) and their emission to the atmosphere and the depletion of the ozone layer. The GHGs, especially carbon dioxide (COz) generated from various combustion activities; methane (CHf generated from rice paddies and flooded areas as a result of anaerobic fermentation, and from ruminating cattle and nitrous oxide (NfO) generated from decomposition of nitrogen fertilizers and livestock wastes trap some of the heat (infrared) that radiate from the earth. The ozone layer at the upper stratosphere which shields the earth specifically from the ultraviolet (UV) light is constantly being destroyed by the immense quantities of chlorine released by volcanoes and other natural emissions, and by chlorine releasedfrom human-made chlorofluorocarbons (CFC, HCFC, HFC, PFC). The most visible effect of climate change is global warming, which has disrupted the thermodynamic balance of the earth, with some regions unnaturally gaining more heat than the others. This rise in earth temperatures has resulted in continued melting of ice caps, glaciers and sea ice, resulting in a rise in global sea levels of between 20cm and 60cm. The Nigerian Niger Delta is under threat of climate related flooding, habitat destruction and species loss. The coastal erosion in the Niger Delta occasioned by sea-level rise is already a menace, especially, regarding destruction of mangrove vegetation which constitutes an important stabilizing system in the brackish ecosystem. Already, 18,803 square kilometers was reported destroyed and 0.21 million people displaced by up to 2-meter coastal sea-level rise. The receipt of increased UV on earth not only increased the temperature on earth, but has serious implications on human health, causing melanoma skin cancer, cataracts and sunburn and altering human's immune system. Afforestation, reforestation, zero-tillage, replacement offossilized fuels with environment-friendly fitels and energy sources like bio-diesel and sustained public awareness programmes are suggested as ways to mitigate the emission of GHGs.